A Bott inverted model for equivariant unitary topological $K$-theory - Spitzweck, Markus; Østvær, Paul Arne (Mathematica Scandinavica, 2010)
Let $\mathsf A$ be an abelian compact Lie group. We show the Bott inverted suspension spectrum of the projective space that classifies $\mathsf A$-equivariant line bundles is a model for $\mathsf A$-equivariant unitary topological $K$-theory.